Trois perspectives lesbiennes féministes articulant le sexe, la sexualité et les rapports sociaux de sexe : Rich, Wittig, Butler - Brossard, Louise (Université du Québec à Montréal, 2004)
Keywords: IREF; approches et analyses; discipline; genre; hétérosexisme; identités; identités LGBTQIA2+; lesbianisme; mémoires/thèses; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

‘I am not Homophobic But...’: Disclaiming in Discourse Resisting Repeal of Section 28 - Burridge, Joseph (Sexualities, 2004)
This article attempts to take seriously the discourse of the morally conservative in the context of the failed repeal of Section 28 in the year 2000, and explores the operation of opposition to repeal which denied that homophobia was its motivation. It is argued that such disclaiming implies an orientation towards an attribution of homophobia as unhelpful or undesirable in this context. The failure of those advocating repeal to successfully problematize such arguments is deemed to reflect a collective ‘discourse of tolerance’ which assisted the arguments of those against repeal.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; homophobie; hétérosexisme; inégalités; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; section 28; soc2014; sociologie; systèmes d'oppressions; thématiques

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (Critical American studies series, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis